Comparative advantage and heterogeneous firms - Andrew B. Bernard; Stephen Redding; Peter K. Schott (Institute for Fiscal Studies (IFS), 2004)
This paper presents a model of international trade that features heterogeneous firms, relative endowment differences across countries, and consumer taste for variety. The paper demonstrates that firm reactions to trade liberalization generate endogenous Ricardian productivity responses at the industry level that magnify countries' comparative advantage. Focusing on the wide range of firm-level reactions to falling trade costs, the model also shows that, as trade costs fall, firms in comparative advantage industries are more likely to export, that relative firm size and the relative number of firms increases more in comparative advantage industries and that job turnover is higher in comparative advantage industries than in comparative disadvantage industries.
Keywords: F11; F12; L11; 330; Heckscher-Ohlin; international trade; inter-industry trade; intra-industry trade; trade costs; entry and exit; Komparativer Kostenvorteil; Produktdifferenzierung; Außenwirtschaftstheorie